Du quilt aux « masques COVID » : L’exercice d’application des normes AFNOR relève-t-il du bricolage de fortune ou du geste de participation civile ? - Trigeaud, Sophie-Hélène (Anthropologica, 2021)
A multitude of masks have been sewn in an attempt to cope with the COVID-19 crisis. The people involved in this fabrication often practice sewing as a hobby or engage in more specialized needlework activities such as patchwork and quilting. However, the production of COVID masks requires the application of precise technical and scientific standards, for instance those of the French standardization authority AFNOR (Association Française de Normalisation). In an ongoing study, we question the passage from one to the other of these activities, with a view to understanding what this production means for those who take part in it. The study is based on an anthropological investigation combining in situ field methods with the exploration of virtual worlds. The seamstresses and tailors involved in the making of masks were interviewed by means of an online questionnaire, which allowed us to meet, despite the health context, the people who engage in this production. Beyond what is sometimes presented as makeshift bricolage, the examination of this mobilization ultimately raises the question of civil participation in times of crisis.